Genome-wide analysis of the Catalpa bungei caffeic acid O-methyltransferase (COMT) gene family: identification and expression profiles in normal, tension, and opposite wood - Nan Lu; Wenjun Ma; Donghua Han; Ying Liu; Zhi Wang; Nan Wang; Guijuan Yang; Guanzheng Qu; Qiuxia Wang; Kun Zhao; Junhui Wang (PeerJ, 2019)
Caffeic acid O-methyltransferase (COMT) is an important protein that participates in lignin synthesis and is associated with the ratio of G-/S-type lignin in plants. COMTs are associated with the wood properties of forest trees; however, little known about the COMT family in Catalpa bungei, a valuable timber tree species in China . We performed a comprehensive analysis of COMT genes in the C. bungei genome by describing the gene structure and phylogenetic relationships of each family member using bioinformatics-based methods. A total of 23 putative COMT genes were identified using the conserved domain sequences and amino acid sequences of COMTs from Arabidopsis thaliana and Populus trichocarpa as probes. Phylogenetic analysis showed that 23 CbuCOMTs can be divided into three groups based on their structural characteristics; five conserved domains were found in the COMT family. Promoter analysis indicated that the CbuCOMT promoters included various cis-acting elements related to growth and development. Real-time quantitative polymerase chain reaction (PCR) analysis showed differential expression among CbuCOMTs. CbuCOMT2, 7, 8, 9, 10, 12, 13, 14, 21, and 23 were mainly expressed in xylem. Only CbuCOMT23 was significantly downregulated in tension wood and upregulated in opposite wood compared to normal wood. Our study provides new information about the CbuCOMT gene family and will facilitate functional characterisation in further research.